Blinded, randomized, sham-controlled clinical trial assessing the efficacy of a novel piezoelectric extracorporeal shockwave device following TPLO - Campbell, Shannon L.; Franklin, Ashley L.; Franklin, Samuel P. (Frontiers in Veterinary Science, 2025)
IntroductionExtracorporeal shockwave therapy (ESWT) devices have been used to effectively treat a wide variety of musculoskeletal conditions in veterinary medicine. However, several factors have limited ESWT device adoption, including that they are commonly loud, uncomfortable, and application typically requires sedation or anesthesia. A novel piezoelectric ESWT device has been developed which is lightweight, quiet, and does not require sedation for application. The purpose of this study is to assess the safety and efficacy of this novel device in clinical application.Materials and methodsThis was a prospective blinded trial in which dogs were randomly allocated to receive three ESWT treatments, or three sham treatments, immediately following and at 2 and 4 weeks post tibial plateau leveling osteotomy (TPLO). The primary outcome measure was clinical function at 4 and 8 weeks post-operatively based on objective gait analysis. Secondary outcome measures included owner subjective assessments (Canine Brief Pain Inventory and Liverpool Osteoarthritis for Dogs questionnaires) at 2, 4, and 8 weeks post-operatively and radiographic assessment of patella tendon thickness and osteotomy healing at 8 weeks post-operatively.ResultsAll dogs completed all ESWT treatments without the need for sedation and no adverse events associated with ESWT use were observed or reported. Dogs in the ESWT group bore significantly more weight at a trot at 4 weeks post-operatively in comparison to dogs in the sham treatment group. There were no statistically significant differences between groups based on owner subjective assessments or radiographic assessments.DiscussionThe study demonstrated that the device was safe and that treatments could be completed without the need for sedation. Subjective owner assessment and radiographic bone healing were not significantly improved with treatment. However, the primary outcome measure, objective gait analysis using a pressure sensitive walkway, showed that dogs in the treatment group bore significantly more weight 4 weeks post-operatively at a trot in comparison to sham-treated dogs.